Domestic Revolution: Aligning Career and Household with Gender Equality Principles - Erandy, Riko; Izzati, Nurul; Darmawan, Aldy (Kawanua International Journal of Multicultural Studies, 2024)
This study examines the roles of husbands and wives in achieving gender equality within dual-income families. Three family types are identified based on employment status: (1) employed husband and unemployed wife, (2) both spouses employed, and (3) employed wife and unemployed husband. Focusing on the second category, this research employs a gender-based approach to analyze the dynamics of dual-career households. The findings reveal five key strategies for realizing gender equality in dual-income families: (1) collaborative decision-making processes, (2) application of socialist principles to household income management, (3) implementation of Ta’awun (mutual assistance) in all aspects of domestic life, (4) development of emotional management skills, and (5) reframing household responsibilities as positive contributions rather than burdens. These complementary roles are proposed as effective measures to address various forms of gender inequality within the family unit, including marginalization (role exclusion), subordination (power imbalance), stereotyping (subjective labeling), violence, and the double burden phenomenon. This research contributes to the ongoing discourse on gender equality in domestic settings and offers practical strategies for couples navigating the complexities of balancing career and household responsibilities.